2013
DOI: 10.14260/jemds/1318
|View full text |Cite
|
Sign up to set email alerts
|

“Grand Multi Parity Still and Obstetric Challenge”- A Clinical Study of Grand Multi Para in a Tertiary Care Center

Abstract: AIMS1. The study aimed to evaluate presence of sexually transmitted infections in pregnant women and to study its distribution in relation to age, parity, social class, habitat and education. 2. To study symptomatology and signs of different sexually transmitted infections in pregnancy and its adverse effects on maternal and pregnancy outcome. MATERIAL AND METHODSSexually transmitted infections in Department of Obstetrics and Gynaecology, Gandhi Medical College, Sultania Zanana Hospital, Bhopal, during 15 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Women's parity was positively associated with postpartum maternal death. This finding was comparable with studies done in Tanzania [63], Nigeria [64], Saudi Arabia [65], and India [66]. The possible justification might be related to pre-existing health conditions of the women, as well as access and utilization of maternity services [67,68] and the combination of these factors may affect the outcome of the mother after delivery.…”
Section: Discussionsupporting
confidence: 86%
“…Women's parity was positively associated with postpartum maternal death. This finding was comparable with studies done in Tanzania [63], Nigeria [64], Saudi Arabia [65], and India [66]. The possible justification might be related to pre-existing health conditions of the women, as well as access and utilization of maternity services [67,68] and the combination of these factors may affect the outcome of the mother after delivery.…”
Section: Discussionsupporting
confidence: 86%
“…The independent variables for this study were identified based on previous studies conducted on the factors affecting grand multiparity at the different places that were reviewed from the literature as associated factors of grand multiparity 11 14 25–35. The independent variables selected for analysis from the available data set were place of residence, maternal age, education status of women, wealth index, current marital status, polygamous marriage, women currently working, religion, husband’s education level, husband’s occupation status, women supported by husband, community media exposure, age of women at first birth, age at first sex, number of living children, preceding birth interval (months), the contraceptive method used, unmet need for contraceptives, the desire for more children, the child being alive, place of delivery and husband’s desire for more children.…”
Section: Methodsmentioning
confidence: 99%